DESIGN OF A PORTABLE COLORIMETRIC SYSTEM BASED ON THE COLOR SENSOR TCS3200 (GY-31) FOR DETECTING THE CONCENTRATION OF METHYLENE BLUE IN SOLUTIONS - Lalu Teguh Permana; Muhandis Siddiq; Husin Alatas; Erus Rustami (Indonesian Physical Review, 2026)
A low-cost colorimetric system based on an Arduino microcontroller and a TCS3200 (GY-31) RGB sensor was investigated to estimate the concentration of methylene blue (MB) in aqueous solutions. Measurements were conducted using a transmission-mode optical configuration, in which a white-light source passes through a cuvette with a fixed optical path length, and the transmitted light is detected as a frequency output. The frequency signal was used as a relative indicator of light intensity, and absorbance was calculated from the ratio of transmitted to reference frequency. Calibration was performed over a concentration range of 0.1–20 ppm, and the results were compared with those obtained using a UV–Vis spectrophotometer. The system showed an approximately linear response to MB concentration with a coefficient of determination (R²) of 0.9807. An average relative error of 18% was observed in the validation results, with limits of detection (LOD) and quantification (LOQ) of 3.95 ppm and 13.17 ppm, respectively. The relatively high LOQ is primarily due to the broadband RGB detection characteristics and signal variability of the low-cost sensor system, which limit sensitivity at low concentrations. Repeated measurements yielded a coefficient of variation below 3%, indicating acceptable short-term repeatability. These results demonstrate the feasibility of the proposed low-cost system for preliminary screening or indicative assessment of MB concentration, particularly at levels near regulatory limits. Further improvements in optical stabilization, spectral selectivity, and calibration procedures are required to enhance sensitivity and accuracy for broader analytical applications.